Gray matter volume covariance networks associated with dual‐task cost during walking‐while‐talking - Tripathi, Susmit (Hum Brain Mapp, 2019)
We studied gray matter volume covariance networks associated with normal pace walking (NPW) speed and dual‐task costs (DTCs) during walking‐while‐talking (WWT)—a mobility stress test that involves walking while reciting alternate letters of the alphabet. Using a multivariate covariance‐based analytic approach, we identified gray matter networks associated with NPW speed (mean 102.1 cm/s ±22.5 cm/s) and DTC (percent difference in gait speed between NPW and WWT, mean 25.9% ± 18.8%) in 139 older adults without dementia (M = 75.3 ± 6.1 years). The gray matter network associated with NPW was primarily composed of supplementary motor area, precuneus cortex, and the middle frontal gyrus. Greater expression of this NPW network was associated with better processing speed (trail‐making test A [r = −0.30, p = 0.005]) and executive function (trail‐making test B − A [r = −0.43, p < 0.0001]). The gray matter network associated with DTC was primarily composed of medial prefrontal, cingulate, and thalamic regions. Greater expression of this DTC network was associated with better episodic memory performance on the free and cued selective reminding test (r = 0.30, p = 0.007). These results suggest that NPW speed and DTC are supported by different networks, and are associated with different cognitive domains.